HUWE1 is a critical colonic tumour suppressor gene that prevents MYC signalling, DNA damage accumulation and tumour initiation. Issue 2 (22nd December 2016) - Myant, Kevin B; Cammareri, Patrizia; Hodder, Michael C; Wills, Jimi; Von Kriegsheim, Alex; Győrffy, Balázs; Rashid, Mamun; Polo, Simona; Maspero, Elena; Vaughan, Lynsey; Gurung, Basanta; Barry, Evan; et al.
Abstract: Cancer genome sequencing projects have identified hundreds of genetic alterations, often at low frequencies, raising questions as to their functional relevance. One exemplar gene is HUWE1, which has been found to be mutated in numerous studies. However, due to the large size of this gene and a lack of functional analysis of identified mutations, their significance to carcinogenesis is unclear. To determine the importance of HUWE1, we chose to examine its function in colorectal cancer, where it is mutated in up to 15 per cent of tumours. Modelling of identified mutations showed that they inactivate the E3 ubiquitin ligase activity of HUWE1. Genetic deletion of Huwe1 rapidly accelerated tumourigenic in mice carrying loss of the intestinal tumour suppressor gene Apc, with a dramatic increase in tumour initiation. Mechanistically, this phenotype was driven by increased MYC and rapid DNA damage accumulation leading to loss of the second copy of Apc . The increased levels of DNA damage sensitised Huwe1 ‐deficient tumours to DNA‐damaging agents and to deletion of the anti‐apoptotic protein MCL1. Taken together, these data identify HUWE1 as a bona fide tumour suppressor gene in the intestinal epithelium and suggest a potential vulnerability of HUWE1 ‐mutated tumours to DNA‐damaging agents and inhibitors of anti‐apoptotic proteins. Synopsis: The E3 ubiquitin ligase HUWE1 is found to be a critical intestinal tumour suppressor gene whose loss of function leads to accelerated tumour initiation via elevated levels of MYC, DNA damage and MCL1. Functionally inactivating HUWE1 mutations are present in primary colorectal cancer samples. Genetic deletion of Huwe1 in an Apc heterozygous mouse model leads to rapid tumourigenesis with a considerable increase in tumour initiation. Huwe1 loss leads to increased MYC protein levels, which increases tumour cell proliferation and accumulation of DNA damage and thus accelerates loss of Apc and drives tumour initiation. Huwe1 ‐deficient tumours show elevated MCL1 levels, which protects them from apoptosis and suggests a vulnerability of HUWE1‐mutated tumours to DNA‐damaging agents and/or BCL2 family inhibitors. Abstract : The E3 ubiquitin ligase HUWE1 is found to be a critical intestinal tumour suppressor gene whose loss of function leads to accelerated tumour initiation via elevated levels of MYC, DNA damage and MCL1.